Mahkota on the Melaka traditional mosques: the study on a visual elements / Raziq Abdul Samat...[et.al] - Abdul Samat, Raziq; Shaari, Shafirah; Hasan, Ahmadrashidi (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
Melaka had been recognized as a World Heritage City by UNESCO in 2008. Based on UNESCO's website, Melaka (along with George Town) . the historic city of Malaysia have developed over 500 years of trade and cultural exchanged between East and West in the Straits of Malacca .With its government buildings, churches, squares and fortifications, Melaka demonstrates the early stages of this history originating in the 15th century Malay sultanate and the Portuguese and Dutch periods beginning in the early 16th century. The two towns constitute a unique architectural and cultural townscape without parallel anywhere in East and Southeast Asia. Based on previous history, it shows that the development and style of arts .culture and architecture are resulted assimilation of foreign countries such as Portuguese. Dutch and British. For an example , the Melaka traditional mosque, there are a lot of assimilation of Chinese. Sumatra n and Indians influence on the architecture itself. The mosque has its own unique identity compare to other mosques in Malaysia.